Physical oceanography from lander deployment DOS-2 during SONNE cruise SO239 - Jens Greinert (PANGAEA, 2018)
Deep-Sea Observation System (DOS) lander from GEOMAR was deployed in the German Prospective Area for a duration about 3 months (2015-03-26 to 2015-06-03). This dataset contains CTD data from Seabird 16plus.